Monday

April 21, 2014

April 21, 2014

Posted by **Steff** on Wednesday, July 13, 2011 at 9:55am.

- Integration by parts -
**Reiny**, Wednesday, July 13, 2011 at 10:45amI would expand it first

∫ (e^x - x)^2 dx

= ∫ e^(2x) - 2xe^x + x^2 dx

let's concentrate on the middle term, since the other two terms are easy to integrate

∫ 2xe^x dx

let u = 2x , let dv = e^x dx

du = 2dx and v = e^x

then ∫ 2xe^x dx = (2x)(e^x) - ∫ 2e^x dx

= 2xe^x - 2e^x

finally ...

∫ (e^x-x)^2 dx

= ∫ e^(2x) - 2xe^x + x^2 dx

= (1/2e^(2x) - (2xe^x - 2e^x) + (1/3)x^3 + c

= (1/2)e^(2x) - 2xe^x + 2e^x + (1/3)x^3 + c

**Related Questions**

Integral calculus - Please can anyone help with the following problems - thanks...

Calculus - How do I integrate (x^2)(e^(x^3)) dx? I think it is integration by ...

calculus - How do I integrate x(arctanx) dx? Is it some sort of integration by ...

Integral calculus - Please do help solve the followings 1) Integrate e^4 dx 2) ...

Math Integration - i keep getting stuck and i think im missing something ...

Competetion help on Integration - If there four options are given to a Defenite ...

Calculus - I have to use integration by parts to integrate tan^-1 (1/x)dx. I'm ...

Math - Indefinite Integration - Use integration by parts to solve: I = f (x^3)(e...

calculus - 1) Integrate Cos^n(x) dx 2) Integrate e^(ax)Sinbx dx 3) Integrate (...

Math/Calculus - How would I integrate the following by parts: Integral of: (x^2...